Lysozyme coated copper nanoclusters for green fluorescence and their utility in cell imaging. Issue 5 (3rd August 2020) - Thawari, Atul Gajanan; Kumar, Piyush; Srivastava, Rohit; Rao, Chebrolu Pulla
Abstract : Green fluorescent, pH dependent and water soluble copper nanoclusters (3–5 nm) were synthesized by stabilizing with lysozyme and these were demonstrated for imaging in both healthy and cancer cell lines as an alternate to green fluorescent protein. Abstract : Fluorescent, pH dependent and water soluble copper nanoclusters (CuNCs) were synthesized using lysozyme (lyz) as the stabilizing agent to give lysozyme coated copper nanoclusters, viz., lyz-CuNCs. The lyz-CuNCs were 3–5 nm in size at neutral pH and exhibit green fluorescence ( λ em ∼ 510 nm) when excited at 490 nm and exhibited a maximum quantum yield of 18%. However, under basic conditions, aggregates of lyz-CuNCs were seen with a particle size of ∼100 nm. The emission of lyz-CuNCs observed at 510 nm complements that from the blue ( λ em = 450 nm) and the red ( λ em = 650 nm) nanoclusters and thus bridges the gap. On the other hand, under acidic conditions, these show a size of 5–10 nm but weakly fluoresce. The particle size and aggregations were monitored by TEM studies carried out using the samples prepared under both the acidic and the basic conditions. The lyz-CuNCs prepared at neutral pH show >90% cell viability and hence can be used as a probe for cellular imaging. The imaging was carried out with both healthy and cancer cell lines, viz., NIH3T3 cells (mouse embryonic fibroblast cell), MCF7 cells (human breast cancer cells) and MDA-MB-231 cells (human estrogen negative breast cancer cells). The Z-stack study suggested the presence of lyz-CuNCs in the cells in cytoplasm. Thus, the green fluorescent lyz-CuNCs can be an alternate to green fluorescent protein (GFP) that is used for cell imaging purposes, since the latter needs a tedious procedure to express, purify and to conjugate.